2006
DOI: 10.1517/14712598.6.3.231
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 as a therapeutic target in head and neck cancer

Abstract: The signal transducer and activator of transcription (STAT) proteins relay signals from cytokine receptors and receptor tyrosine kinases on the cell surface to the nucleus, where they affect the transcription of genes involved in normal cell functions, including growth, apoptosis and differentiation. STAT3 has been found to be constitutively active in head and neck squamous cell carcinoma (HNSCC) as well as in other epithelial malignancies. In HNSCC, STAT3 alters the cell cycle, prevents apoptosis, and mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(172 citation statements)
references
References 114 publications
3
167
0
Order By: Relevance
“…A number of findings indicate that STAT3 is constitutively activated and participates in the regulation of cell proliferation, differentiation and apoptosis in HNSCC (17,18). Aberrant STAT3 activation, manifested by increases in STAT3 tyrosine phosphorylation, is considered as a potent promoter of HNSCC initiation and progression, thereby inhibition of STAT3 has been identified as a potential therapeutic target for the treatment of HNSCC (16,18,62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of findings indicate that STAT3 is constitutively activated and participates in the regulation of cell proliferation, differentiation and apoptosis in HNSCC (17,18). Aberrant STAT3 activation, manifested by increases in STAT3 tyrosine phosphorylation, is considered as a potent promoter of HNSCC initiation and progression, thereby inhibition of STAT3 has been identified as a potential therapeutic target for the treatment of HNSCC (16,18,62).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant STAT3 activation, manifested by increases in STAT3 tyrosine phosphorylation, is considered as a potent promoter of HNSCC initiation and progression, thereby inhibition of STAT3 has been identified as a potential therapeutic target for the treatment of HNSCC (16,18,62). STAT3 constitutive activation in HNSCC is driven by a number of upstream signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STAT3 signalling pathways regulate the gene expression of proliferation, survival, migration and invasion, as well as angiogenesis (2,20) in human. Furthermore, STAT3 is essential at early stages of embryo development (21) and modulates embryonic stem cell differentiation such as TH17 helper T cells (22).…”
Section: Biology Of Stat3mentioning
confidence: 99%
“…Several dysregulated proinflammatory signaling cascades including NF-kB, STAT3, and serine/threonine protein kinase B (AKT) have been linked to the carcinogenesis of HNSCC and play a pivotal role in the growth, proliferation, and survival of the head and neck cancer (6)(7)(8)(9)(10). For example, Sen and colleagues recently reported that STAT3 activation can even contribute to EGF receptor inhibitor resistance in HNSCC and thereby targeting of STAT3 may represent an effective treatment strategy (10).…”
Section: Introductionmentioning
confidence: 99%